Regulation of the oncoprotein Smoothened by small molecules - Sharpe, Hayley J; Wang, Weiru; Hannoush, Rami N; de Sauvage, Frederic J (Nature chemical biology, 2015)
This Perspective discusses recent advances in understanding the structural and pharmacological properties of the downstream Hedgehog pathway effector Smoothened. Small molecule agonists and antagonists of Smo could be used as potential therapeutics. The Hedgehog pathway is critical for animal development and has been implicated in multiple human malignancies. Despite great interest in targeting the pathway pharmacologically, many of the principles underlying the signal transduction cascade remain poorly understood. Hedgehog ligands are recognized by a unique receptor system that features the transporter-like protein Patched and the G protein–coupled receptor (GPCR)-like Smoothened (SMO). The biochemical interaction between these transmembrane proteins is the subject of intensive efforts. Recent structural and functional studies have provided great insight into the small-molecule regulation of SMO through identification of two distinct ligand-binding sites. In this Perspective, we review these recent findings and relate them to potential mechanisms for the endogenous regulation of SMO.